PID controller based on artificial intelligence : Applied to different models - Ahmed Abdelhaleem Mohammed Salem; Mohamed Ahmed Moustafa Hassan; Mohammed Elsayed Ammar (Cairo : Ahmed Abdelhaleem Mohammed Salem, 2014)
The PID controllers are the most commonly used controller structures in industry. The main challenge is in the aspect of tuning of the gains. There are several traditional techniques introduced by Ziegler and Nichols but it is inefficient. In this thesis, it is proposed that the PID controller tuned based on the Artificial Intelligence techniques (the GAs, the Improved Genetic Algorithms and finally the PSO). Then applied all techniques to different applications (DC-Motor and AVR System), from the results the techniques based on Artificial intelligence are better than traditional techniques
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Electrical Power and Machines
Issued also as CD
Keywords: AVR system; DC-Motor; PID-controller